2020
DOI: 10.1016/j.celrep.2020.107744
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Arginine Methyltransferase PRMT8 and Substrate G3BP1 Control Rac1-PAK1 Signaling and Actin Cytoskeleton for Dendritic Spine Maturation

Abstract: Highlights d PRMT8 is upregulated in hippocampus during dendritic spine maturation d Depletion of PRMT8 generates more filopodia d Lack of PRMT8 increases cofilin phosphorylation and slows actin turnover d Spine maturation depends on arginine methylation of the PRMT8 substrate G3BP1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 104 publications
3
43
0
Order By: Relevance
“…In mice, persistent stress caused by the absence of PRMT8 activity decreases activation of pro-survival and regeneration pathways, even under aging-related oxidative and ER stress, ultimately leading to a progressive loss of muscle strength because of premature destabilization of neuromuscular junctions (Simandi et al, 2018). Moreover, PRMT8 expression is increased in the hippocampus during spine maturation and depletion of PRMT8 impairs spine maturation and alters actin dynamics; importantly, these phenotypes are mimicked by G3BP1 depletion (Lo et al, 2020). Thus, defects in the motor neuron-specific methyltransferase PRMT8 induce G3BP1 dysfunction, developmental problems, and accelerated aging that could potentially be rescued by G3BP1 activity.…”
Section: Post-translational Modifications Of G3bp1 Affect Stress Granule Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, persistent stress caused by the absence of PRMT8 activity decreases activation of pro-survival and regeneration pathways, even under aging-related oxidative and ER stress, ultimately leading to a progressive loss of muscle strength because of premature destabilization of neuromuscular junctions (Simandi et al, 2018). Moreover, PRMT8 expression is increased in the hippocampus during spine maturation and depletion of PRMT8 impairs spine maturation and alters actin dynamics; importantly, these phenotypes are mimicked by G3BP1 depletion (Lo et al, 2020). Thus, defects in the motor neuron-specific methyltransferase PRMT8 induce G3BP1 dysfunction, developmental problems, and accelerated aging that could potentially be rescued by G3BP1 activity.…”
Section: Post-translational Modifications Of G3bp1 Affect Stress Granule Assemblymentioning
confidence: 99%
“…Summary of G3BP1 post-translational modifications and their effects on the proteinLo et al, (2020) reported as R433 and R445 of the mouse sequence corresponding to R435 and R447 of the human sequence.2007). While HDAC6 is known to have pleiomorphic effects, it is noteworthy that HDAC6 down-regulation is observed in several neurodegenerative diseases including AD, PD, and HD, and HDAC6 is regulated by TDP-43(Fiesel et al, 2010;Simões-Pires et al, 2013).…”
mentioning
confidence: 99%
“…These alterations in synaptic function were not accompanied by detectable changes in brain or neuron morphology. Context-dependent fear learning was impaired but locomotor or anxiety-related behaviors were not altered in Prmt8 conditional knockout mice [ 58 ], differing from the behavioral phenotypes described by Kim et al [ 54 ] and Lo et al [ 59 ] that reported reduced anxiety in open field and elevated plus maze paradigms.…”
Section: A Role Of Protein Arginine Methylation In Dendritic Spine Formation and Maturation—signaling To Actin Cytoskeletal Factors?mentioning
confidence: 99%
“…Recently, a role for the arginine methylation activity of PRMT8 in dendritic spine maturation that involves signal cascades targeting neuronal actin dynamics has been reported [ 59 ] ( Figure 3 ). shRNA-mediated knockdown of PRMT8, which localizes to postsynaptic sites overlapping with PSD-95 in primary hippocampal neurons, resulted in a decreased density of mushroom spines but increased filopodia density.…”
Section: A Role Of Protein Arginine Methylation In Dendritic Spine Formation and Maturation—signaling To Actin Cytoskeletal Factors?mentioning
confidence: 99%
See 1 more Smart Citation